Research handbook on homelessness - Johnson, Guy; Culhane, Dennis P.; Fitzpatrick, Suzanne; Metraux, Stephen; O'Sullivan, Eoin (Edward Elgar Publishing, 2024)
"The Research Handbook on Homelessness presents a comprehensive account of the current knowledge and understanding of homelessness, the substantial challenges it presents and the latest developments in responding to the issue. Bringing together 53 of the world's leading scholars in this field, this multidisciplinary Research Handbook acknowledges the increasing interest in homelessness across various academic disciplines and highlights the constant evolution of this issue, as well as the research methods that accompany it. Contributing authors discuss homelessness image control, the cost of homelessness, and the role of the welfare state, as well as a seminal section dedicated to the impact of COVID-19 on homelessness policy and research. Looking ahead, the book points to future research possibilities which will address the structural factors that drive homelessness and encourage effective reforms of social housing systems. This insightful book is a vital read for academics, researchers and students specialising in welfare economics, human geography, health policy and economics, and comparative social policy. Including a breadth of research summaries and case studies, the book will also be invaluable to policymakers working in the homelessness field and in allied areas such as health and justice"--